Just price theory : historical perspectives and contemporary insights - Petersen, Mati??as; Reyes, Joaqui??n (Law teacher) (Routledge, 2026)
"This book presents an interdisciplinary approach to just price theory, focusing on the conceptual and normative (moral, legal, and political) implications of the concept of the just price. This volume brings together world-leading experts in the fields of political and legal philosophy to explore the political economy of justice in pricing and socio-legal aspects surrounding the idea of just prices. Divided in two parts, the first set of essays explores the relevance of various normative criteria that might serve as a benchmark for assessing market prices from the standpoint of justice. The second part of the book addresses some of the institutional factors that are relevant in discussions about justice in pricing, exploring the role that legal and social norms play in evaluating whether market institutions are justice-preserving or not. Perfect for scholars and students in the fields of jurisprudence, ethics, political philosophy, philosophy of economics, and private law theory"-- Provided by publisher.
Keywords: Price regulation.; Price regulation -- History.; Price regulation -- Political aspects.; Price maintenance -- Law and legislation.; Price discrimination.; Prices -- Moral and ethical aspects.; elektronické knihy; electronic books